Implementing kiva antibullying program in pioner schools in Spain - López-Catalán, Blanca; Mäkela, Tiina; Sánchez Sánchez, Francisca; López-Catálan, Luis (IJERI: International Journal of Educational Research and Innovation, 2022)
This study analyzes the implementation of the KiVa Antibullyiing program in Spain with 10 pioneer schools. This research has two aims. The first is a preliminary evaluation of the KiVa program’s implementation in the pioneer schools in Spain. To do so, the perceived levels of bullying and victimization have been analyzed through the surveys done anonymously by the students of 10 KiVa schools before and after the program’s implementation. The second is to identify the factors which explain the phenomenon with a view to knowing the background of the victims and the bullies and proposing courses of action. To do so, the school environment (atmosphere in the classroom and in the school), the perception of the students concerning teachers and parents in relation with the phenomenon (attitude, capacity and behavior) and the communication of the victims were analyzed in their environment in the case of bullying. In the empirical study, analyses were performed of the prevalence of bullying before and after the first year of program’s implementation, as well as an analysis of independence and multiple correspondences. This enables identifying the key variables and drawing conclusions about how the children surveyed live out school bullying in the pioneer Spanish KiVa schools, and what aspects should guide other schools interested in preventing bullying.